التوازن بين مسؤوليتي المؤجر والمستأجر في عقد التأجير التمويلي : دراسة في التشريع الأردني - المولى، نداء كاظم محمد جواد (جامعة الزرقاء - عمادة البحث العلمي, 2013)
عقد التأجير التمويلي عقد حديث النشأة ومعقد ومركب في طبيعته وآثاره، يأخذ صيغة عقد الإيجار، إلا إنه بخرج عن هذا الوصف في كثير من التزاماته. يرتب التزامات متفاوتة على كلا طرفيه، تمثيل شدة على المستأجر وتخف على المؤجر، مما يعطي انطباعا بعدن التوازن بين تلك الالتزامات المتبادلة. وينعكس هذا الأمر على مسؤولية طرفي العقد. فيسأل المستأجر عن فعله الشخصي وعن فهل الغير، والأشياء، علاوة على تحمله القوة القاهرة. في المقابل نجد إن المؤجر يحاول التخفيف من مسؤوليته، من خلال ما يتضمنه العقد من اتفاقات تبعده عنها؛ لأنه يهدف في الأساس إلى استثمار أموله في عملية تمويل المأجور وشرائه؛ ثم تأجيره إلى المستأجر، الذي يستغله، ومن ثم يتملكه نهاية مدة الإيجار، إضافة إلى تحقيق فوائد أخرى كثيرة تجعله يقبل تحمل المسؤولية الثقيلة التي يفرضها عليه المؤجر دون تردد، ويتلافى نتائج المسؤولية تلك من خلال عقود أخرى، لإبعاد هذه المسؤولية أو التخفيف من نتائجها، ومن تلك العقود عقد التأمين، وعقد البيع، والوعد بالتعاقد... ولتحليل ذلك فقد تناولت في الدراسة تحليل عقد التأجير التمويلي من خلال تعريفه، وبيان خصائصه، وطبيعته، وآثاره، لإبراز مسؤولية طرفي العقد، وبيان الجد الذي يمكن أن يحقق التوازن بينهما، ثم النتائج التي ترتبت على الدراسة. The financial leasing contract is a new and complicated one both in nature and consequences. It takes the form of a rent contract, yet it extends to more than this description in many of its obligations. Its consequences and obligations are severer on the tenant than on the lessor, which gives the impression of imbalance between these mutual obligations. This is reflected on both parties of the contract. The tenant is asked not only about his actions but even about what others do; in addition to the great burden he bears. On the other hand, we notice that the lessor tries to loosen his responsibilities, by the various terms he includes in the contract. This happens due to the fact that the lessor aims essentially to invest his money in the process of financing, buying the rented property, and then rent it to the tenant who, on his part, uses the property then owns it eventually at the end of the leasing period. Owning the house at the end of the period- in addition to the other benefits compels the tenant to accept the heavy responsibility imposed on him by the lessor without any hesitation. He avoids the consequences of such responsibility through other contracts that shun or mitigate it. Such contracts include the insurance contracts, selling contracts and promise to contract. To clarify this, I attempted, in this study, to analyze the financial leasing contract through defining it, and discussing its characteristics and the nature of its consequences, in order to emphasize the responsibility of the two contracted parties, as well as defining the limits that achieve balance between them. Finally, the results of this study are stated.
Keywords: عقود الأيجار -- العقارات -- التأجير التمويلي -- القوانين والتشريعات -- الاردن